THE URGENCE OF LEGAL AWARENESS IN THE BENEFICIARIES OF THE PROGRAM KELUARGA HARAPAN (PKH) IN OKU TIMUR DISTRICT - Hendri Irawan; Dadang Sundawa; Iim Siti Masyitoh (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
In essence, every human being is a creature who always seeks peace and tranquility in his life. In realizing this, it is necessary to have a rule that binds and regulates to be applied in everyday life. One of the people who must have good legal awareness is the beneficiary family of the Family Hope Program (PKH) which is able to implement their rights and obligations in spending assistance that has been provided by the government in accordance with predetermined rules. The purpose of this study is to analyze the urgency of legal awareness in society, especially legal awareness in the Family Hope program in East Ogan Komering Ulu Regency. The method used in this writing is using a qualitative descriptive approach with two sources of data, namely primary data through interviews with beneficiary families (PKH) and direct involvement in field socialization and secondary sources in the form of journals, relevant articles and related photos. The results of this writing are the importance of legal awareness in PKH which includes three components including; welfare, education and health which are still not fully implemented researchers provide a solution for increasing legal awareness in the community of (PKH) through outreach to the community regarding the importance of using and spending appropriate assistance as an effort to improve family welfare in order to realize the ideals of the Indonesian state contained in the 1945 Constitution of the Republic of Indonesia.